MiR‐181a/b therapy in lung cancer: reality or myth?. Issue 1 (3rd January 2019) - Braicu, Cornelia; Gulei, Diana; Cojocneanu, Roxana; Raduly, Lajos; Jurj, Ancuta; Knutsen, Erik; Calin, George Adrian; Berindan‐Neagoe, Ioana
Abstract : Despite substantial progress in oncology, lung cancer remains the number one malignancy in terms of both incidence and mortality rates, and there thus remains an urgent need for new therapeutic alternatives. MicroRNA (miRNA) have an important role in cancer initiation and progression due to their capacity to interfere with transcriptional signaling and regulate key cellular processes. miR‐181a and miR‐181b (miR‐181a/b), which are located on chromosomes 1 and 9, are pathologically expressed in the tumor tissue and plasma of patients diagnosed with lung cancer. The miR‐181a/b regulatory mechanisms are sophisticated and are directly related to different target genes. In recent years, an ever‐increasing number of studies have focused on the biological relevance of miR‐181a/b in key cellular processes. In this paper, we aim to discuss the challenging experimental data related to miR‐181a/b and their potential use for the development of new therapeutic approaches in lung cancer. We will further present the ongoing issues regarding the regulation of their multiple target genes, and their potential use as biomarkers and therapeutic targets in this deadly malignancy. Abstract : miR‐181a/b are generally downregulated in lung cancer, and the expression of both is associated with an unfavorable prognosis. Differential expression patterns are observed in different cells and under context‐specific conditions. miR‐181a/b regulate structural and cellular elements involved in cell proliferation, drug resistance, cell plasticity, and adaptive programs favoring cancer evolution. Here, we comprehensively describe the expression and mechanisms associated with miR‐181a/b, and indicate their therapeutic and diagnostic/prognostic biomarker value.